PROJECT BASED LEARNING IN DESIGNING ENGLISH FOR WETLAD TO PROMOTE 21ST CENTURY EDUCATOR - Nasrullah Nasrullah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
21st century educators employ multirole in conducting the teaching and learning process such as being a leader, facilitator, model, communicator, adaptor, risk taker, and also learner. An effort to involve all those qualities as well as the role of teacher as a learner can be provided in a way that collaboration between teacher and learners exists in selected project based activities. This paper reflects project based activity in learning English for Wetland subject in a special (local) locus where this course in learned. The approach used in investigating the research objective is qualitative. Descriptive research is also chosen to explore and describe the existing phenomena. To get the data, researcher uses triangulation [observation, interview and document analysis]. Moreover, this study uses 35 subjects of research to collect the data. The findings of this study are in the forms of wetland vocabularies [flora and fauna] based on the selected areas investigated, certain English described phenomena in wetland area and info graphical media in which that two previous information is elaborated.